Development and characterization of creamy sweet from pomace vinified grape (Research, Society and Development, 2020)
The aim of this study was to develop and characterize creamy sweet from the pomace of vinified Vitis vinifera grapes. The pomace was selected and characterized by physical-chemical, microbiological and bioactive compounds analyzes. After processing, two creamy sweets were formulated, one with industrial pectin (Pectin) and other with agar gum and carrageenan (Gums). The creamy sweets were characterized by physical-chemical, microbiological, bioactive compounds, rheological and sensory tests. Mold and yeast count was higher (p